Analysis of tourist motivation for traditional culinary tourism in Bogor - Bonanza Occy; Sofiantina Rahayu Kania; Prabandari Dyah; Patabang Melewanto; Lidya Leni (E3S Web of Conferences, 2023)
Bogor is a city that represents a blend of traditional Sundanese culture, colonial culture, and the modernity of a metropolitan city. A variety of culinary are offered, ranging from regional to traditional specialties. This condition encourages research on tourist motivation in traditional culinary tours in Bogor. Analysis of tourist motivation in traditional culinary tours can be the basis for developing culinary tourism areas in Bogor. The methods used in the research were observation, interviews, and questionnaires to 50 traditional culinary tourists from Bogor. The questionnaire contains the characteristics and motivations of tourists in culinary tours in Bogor. The collected data were analyzed using the Confirmatory Factors Analysis (CFA) statistical test. This study shows that the indicators of latent motivation have a significant and valid effect. Physical motivation, an indicator that reflects the condition of tourists in traditional culinary tourism activities, relieves fatigue. Furthermore, on cultural motivation, an indicator that reflects the condition of tourists is the desire to taste food. For social motivation, an indicator that reflects the condition of tourists is visiting family, and for status motivation, an indicator that reflects the condition of tourists is taking pictures at event venues/culinary activity centers.